3-D density imaging with muon flux measurements from underground galleries. Issue 3 (23rd December 2016) - Lesparre, N.; Cabrera, J.; Marteau, J.
Summary: Atmospheric muon flux measurements provide information on subsurface density distribution. In this study, muon flux was measured underground, in the Tournemire experimental platform (France). The objective was to image the medium between the galleries and the surface and evaluate the feasibility to detect the presence of discontinuities, for example, produced by secondary subvertical faults or by karstic networks. Measurements were performed from three different sites with a partial overlap of muon trajectories, offering the possibility to seek density variations at different depths. The conversion of the measured muon flux to average density values showed global variations further analysed through a 3-D nonlinear inversion procedure. Main results are the presence of a very low density region at the level of the upper aquifer, compatible with the presence of a karstic network hosting local cavities, and the absence of secondary faults. We discuss the validity of the present results and propose different strategies to improve the accuracy of such measurements and analysis.